THE LEGAL FRAMEWORK OF THE EUROPEAN UNION TOWARDS CRITICAL INFRASTRUCTURE - Poposka, Vesna; Oktay, Hasan (International Scientific Journal Vision, 2021)
Critical infrastructure protection is crucial to enrich and develop the four main freedoms of movement that settle the single European market. Besides, due to the recent developments related to the pandemic and energy crisis, the critical infrastructure development and protection gets different dimension. The EU has followed a sectoral approach in this area, with activities scattered across spheres of action led by a variety of institutional actors. In principle, this provides an adapted approach to different integrity needs and different legal competencies within the policy spectrum, but as will be discussed later in this paper , this also has important implications for a coherent and holistic European response. Although there are several sectoral legal bases for the protection of critical infrastructure at EU level (for example, in the transport and energy sectors), the founding agreements do not directly address critical infrastructure protection issues directly. Although the milestones of the protection of critical infrastructure were settled more than a decade ago, the basic framework has not changed much a cornerstone of action that generates and allocates funding through different programs and projects. The paper aims to provide overall framework and general vision over the framework of activities in the area that is pretty diverse.